Comparative analysis of FDI duration in the Visegrád Group member states, using mortality tables: A sectoral approach - Salamaga, Marcin (Analiza porównawcza trwania BIZ w krajach wyszehradzkich z wykorzystaniem tablic wymierania – ujęcie sektorowe, 2022)
FDIs are an important part of the ‘bloodstream’ of many countries’ economies, and it would be difficult to overestimate the benefits of FDIs for the states that receive them. The processes of FDI influx and their effects have been the subject of numerous studies and analyses in the fields of both economic theory and empirical research. However, less attention has been paid to the process of divestment, which in many cases may result in adverse changes in the economies of FDI recipient countries. This article proposes that event history analysis methods can be used to study the survival of FDI projects. FDIs are launched at a certain point in time by investors, last for some time, and then can be either terminated or continued. In this context, we may come across complete as well as truncated observations, much like in the analyses of population processes, therefore the use of demographic methods to study the survivability of FDI projects is justified. The purpose of this article was to present specially constructed FDI life tables and to compare the ‘survivability’ patterns of foreign direct investments in selected economic sectors of the Visegrád Group countries. For many years, these countries have enjoyed considerable interest from foreign investors and have often competed with each other for new FDI projects. Therefore, comparing them not only in terms of the processes related to FDI influx, but also in terms of the processes of divestment appears interesting and important to economists, market analysts and the investors themselves. The study used data from the Orbis and Zephyr databases.
Econometrics = Ekonometria, 2022, Vol. 26, No. 2, s. 1-14
Keywords: life table; hazard rate; FDI; divestment; tablice trwania życia; stopa hazardu; BIZ; dezinwestycja